2014
DOI: 10.2147/opth.s63915
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods of tonometry in normal subjects: Goldmann applanation tonometer, non-contact airpuff tonometer, and Tono-Pen XL

Abstract: Objective: We aimed to compare intraocular pressure (IOP) measurements via three different tonometers: the Goldmann applanation tonometer (GAT), the Tono-Pen ® XL (TPXL), and a non-contact airpuff tonometer (NCT).Methods: This was a cross-sectional study of 200 eyes from 200 patients. Right eyes of all patients were included in this study. IOP was measured via GAT, NCT, and TPXL by three physicians. Each physician used one of the tonometers. Measurements via the three devices were compared. Results: The mean I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
3
33
0
5
Order By: Relevance
“…Non-contact tonometry has been shown to overestimate IOP relative to applanation tonometry in some studies, 26,27 while others have reported similar results between the two methods. 28,29 A number of studies have noted better intra-and interoperative reproducibility of IOP measurements with Goldman applanation tonometry and dynamic contour tonometry (DCT) compared with non-contact methods. [30][31][32] The influence of central corneal thickness and corneal curvature on IOP readings has also been reported to differ among individual measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Non-contact tonometry has been shown to overestimate IOP relative to applanation tonometry in some studies, 26,27 while others have reported similar results between the two methods. 28,29 A number of studies have noted better intra-and interoperative reproducibility of IOP measurements with Goldman applanation tonometry and dynamic contour tonometry (DCT) compared with non-contact methods. [30][31][32] The influence of central corneal thickness and corneal curvature on IOP readings has also been reported to differ among individual measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This device is particularly useful with corneal scars or edema. 121,123,172,192 Because it is portable, it is useful in the office setting as well as during an EUA ( Fig. 5).…”
Section: Tono-pen Applanation Tonometrymentioning
confidence: 99%
“…Some research suggested that IOP NCT had good repeatability and precision. 20 This tonometer records three readings and then calculates the average value automatically.…”
Section: Noncontact Tonometermentioning
confidence: 99%